The athecatae hydroids (Cnidaria, Hydrozoa) from Northern Bahía, Brazil - Kelmo, Francisco (1998)
We provide a taxonomic account of the athecatae hydroids taxonomic known from northern Bahia, down to a depth of 60 m, based largely on collections made by the authors since 1992. All colonies were collected along the coast of Salvador City, at Todos os Santos Bay, in Itaparica Island and at the northern most part of the coast of the Stale of Bahía. The 226 colonies obtained are stored at the Scientific Collection of the Departamento de Zoologia do the Instituto de Biologia da Universidade Federal da Bahía (UFBA,CNI-HYD),The studied athecatae faunais represented by nine species. This fauna is rather depauperate, accounting for only about one-third of the total number of hydroids recorded from Brazil. A simplified identification key, redescriptions; illustrations, and data on nematocysts complement and size are provided for each species. Rhizodendrium sterreri and Parawrightia robusta are reported from Brazil for the first time.